Efficacy of Non-invasive Brain Stimulation Methods for the Treatment of Cognitive Impairment in Traumatic Brain Injury and Stroke - Mariam Kavakcı (Türk Nöroloji Dergisi, 2021)
Cognitive impairments are pervasive among populations with traumatic brain injury and cerebral vascular accidents. Given the limited effectiveness of behavioral approaches in treating cognitive impairments, the use of non-invasive brain stimulation and modulation methods have been increasingly explored over the past decade. The present article reviews recent evidence on the use of two non-invasive technologies, transcranial magnetic stimulation and transcranial direct current stimulation on populations with brain injury and stroke. The results indicate that although evidence for the use of neuromodulation for cognitive enhancement in neurotypical adults is somewhat positive, its use in disordered populations is less promising. Few studies demonstrated positive effects of neuromodulation on cognitive measures. Importantly, most results are confounded by behavioral interventions and the effects are highly variable. More research is needed to evaluate the therapeutic potential of non-invasive brain stimulation techniques when used in isolation for remediation of cognitive impairments associated with various neurologic conditions. Larger clinical trials with strong methodologic rigor including double-blind randomized control trials are necessary to validate the use of these methods for translational implementation. Given the conflicting evidence base that presently exists, when neuromodulation techniques are employed, they should be used with cognitive and physical therapies that are given precedence.